A Modified Thermal Decomposition Approach for The Synthesis of Phase-Pure YBa₂Cu₃O₇−δ Superconductor - Dzul-Kifli, Nur Athirah Che; Zakaria, Nurul Zafirah; Kechik, Mohd Mustafa Awang; Kien, Chen Soo; Pah, Lim Kean; Shaari, Abdul Halim; Shabdin, Muhammad Kashfi; Doyan, Aris; Hong, Yap Siew; Hapipi, Nur Hidayah Mohd (Balai Publikasi Indonesia, 2026)
High temperature superconductor of YBa2Cu3O7-δ (Y-123) has been synthesised using the modified thermal decomposition method (MTD). In this work, a pure Y-123 sample is produced using an acetate-based material as a precursor and sintered at 980 oC. The study on the phase formation, superconducting properties and microstructural characteristics of pure Y-123 was investigated using X-ray diffraction (XRD), four-point probe (4PP) and scanning electron microscopy (SEM) respectively. XRD analysis confirmed the formation of a single-phase orthorhombic Y-123 crystal structure with an orthorhombicity of 0.008, indicating high phase purity without detectable impurity phases. Electrical measurements revealed a sharp superconducting transition with a critical onset temperature, Tc-onset of 97.3. SEM observations showed plate-like grains with an average grain size of 2.25 µm and good grain connectivity. These results demonstrate that the modified thermal decomposition technique is an effective approach for producing phase-pure YBCO superconductors with excellent structural and superconducting properties, highlighting its potential for advanced superconducting applications